Design of an interlocked four-port MIMO antenna for UWB automotive communications. Issue 2 (23rd March 2022) - Saravanan, M.; Kalidoss, R.; Partibane, B.; Vishvaksenan, K. S.
Abstract: The design, analysis, fabrication, and testing of a four-port multiple-input multiple-output (MIMO) antenna is reported in this paper for automotive communications. The MIMO antenna is constructed using the basic antenna element exploiting a slot geometry. Two such antennas are developed on the same microwave laminate to develop a two-port MIMO antenna. Two such microwave laminates are interlocked to create the four-port MIMO scheme. The most distinct feature of the proposed architecture is that the inter-port isolation is well-taken care without the need for an external decoupling unit. The four-port MIMO antenna has an overall volume of 32 × 15 × 32 mm 3 . The prototype MIMO antenna is fabricated and the measurements are carried out to validate the simulation results. The antenna offers ultra-wideband (UWB) characteristics covering the frequency range of 2.8–9.5 GHz. The average boresight gain of the antenna ranges from 3.2 to 5.41 dBi with the peak gain at 8 GHz. The simulated efficiency of the antenna is greater than 73% within the operating bandwidth. The MIMO parameters such as envelope correlation coefficient, diversity gain, and mean effective gain are evaluated and presented. The appropriateness of the proposed antenna for deployment in the shark fin housing of the present-day automobiles is verified using on-car performance estimation.